Estimativas de funções de covariância para características de crescimento da raça tabapuã utilizando modelo de regressão aleatória - Sousa Junior, Severino Cavalcante de (2007)
The study used 28,873 weight records taken along the life of 6.471 animals of the race Tabapuã, finery birth to 660 days of age, belonging to the animal archives of the Brazilian Association of Zebu Breeders (ABCZ) to estimate the covariânce functions using the models of random regression. The genetic, addictive direct an permanent environmental effects were used as random effects the contemporary groups as fixed effects. The average age of the cows at delivery as covariavel (linear and quadratic). The residue was modeled by functions of variances of quadratic order. The analyses with orthogonal polynomials were performed for the direct genetic effect, genetic of animal permanent environment atmosphere of linear and quadratic. Models were compared by the Bayesian of information criteria of Schwarz (BIC) and of Akaike (AIC). The heritability estimates for the direct effects were greater in the beginning and by the end of the studied period, with values of 0,48 at birth, 0,27 to the 240 days and 0,14 to the 660 days of age. The genetic correlations varied from moderate to high, reducing as intensity in proportion to the increase of the increase of distance between ages the distance accordingly among the ages.